Quantum Computing: Revolutionizing Advanced Risk Management Systems - Pradeep Kumar Chilukury, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines how quantum computing revolutionizes sophisticated risk management systems in several industries, focusing on cybersecurity and financial services. It looks at how quantum computing technology transforms conventional risk assessment methods, fraud prevention, and security architecture by utilizing quantum bits and the concepts of superposition and entanglement. The creation of quantum-resistant cryptographic algorithms, the application of quantum-enhanced probabilistic analysis for financial risk management, and the obstacles to the broad adoption of quantum computing are all examined in this article. The article illustrates the substantial potential of quantum computing in enhancing risk management frameworks while stressing the factors that must be considered for successful adoption by examining current market trends, technological advancements, and industry applications. The convergence of quantum computing with other cutting-edge technologies like blockchain and artificial intelligence for improved risk management capabilities is also examined, as are the broader ramifications for industries other than finance, such as healthcare, manufacturing, and telecommunications.
Keywords: Quantum Computing; Risk Management; Cybersecurity; Financial Technology; Quantum Cryptography